Effect of Work Stress, Environment, and Leadership Style on the Performance of Retail Store Employees in Tangerang District (Case Study of Retail Stores in Tangerang Regency) - Bobby Reza; Anis Cahyati (Enrichment : Journal of Management, 2021)
This type of research is quantitative research. The number of population in this study is unknown, so the researcher uses the Saturated Sample formula to determine the sample using the Saturated Sample Technique, ie all members of the population are sampled. The technique used for the sample size in this study is the saturated sample formula with a sample of 100 respondents. Data analysis using descriptive analysis test, validity test, reliability test, classical assumption test, normality test, homogeneity test, multiple linear regression analysis test, hypothesis test, t test, f test, and coefficient of determination test. The results of the work stress research obtained a correlation coefficient of 0.281, meaning that the work stress variable has a relationship level. Hypothesis test t-count > t-table or equal to (2.101 > 1.984), this is also strengthened by the value < sig 0.05 or (0.000 < 0.05). Thus, work stress has a significant effect partially on employee performance. The results of the research work environment obtained a correlation coefficient value of 0.465, meaning that the work environment variable has a relationship level. Hypothesis test t-count > t-table or (3.640 > 1.984), this is also strengthened by the value of p Value < sig (0.000 < 0.05). Thus the work environment has a significant partial effect on employee performance. The results of the leadership style research obtained a correlation value of 0.257, meaning that the leadership style variable has a relationship level. Hypothesis test t-count > t-table or (2.025 > 1.984), this is also strengthened by the p value < sig (0.000 < 0.05). Thus, leadership style has a significant partial effect on employee performance. Work stress, work environment, and leadership style have an f-count > f-table (6.728 > 2.70) with a significance value of p value < sig (0.000 < 0.05) so for the variables of work stress, work environment, and style leadership has a simultaneous influence on employee performance. the results of multiple linear regression calculations (r-square) of 0.837 so it can be concluded that the performance of employees at retail store employees in kab. Tangerang can be explained by 83.7% by the variables of work stress, work environment, and leadership style on employee performance (strong category) while the rest (16.3%) is influenced by other factors.